2022
DOI: 10.2147/ijwh.s345454
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of Botulinum Toxin Bladder Injection for the Treatment of Refractory Overactive Bladder

Abstract: Intradetrusor botulinum toxin injections is an established second-line treatment for patients with refractory overactive bladder syndrome (OAB). We aimed to evaluate the learning curve of intradetrusor injections with botulinum toxin for the treatment of refractory OAB. Patients and Methods: This retrospective study analyzed all women with idiopathic and refractory OAB who underwent botulinum toxin bladder injections performed by residents with no previous experience with operative cystoscopy under consultant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Rates of CIC requirement after BTX-A injection into the bladder are highly variable, ranging from 4% to 45% of cases. In other worldwide clinical trials, the mean CIC rate was approximately 23% of cases [21,22].…”
Section: Discussionmentioning
confidence: 88%
“…Rates of CIC requirement after BTX-A injection into the bladder are highly variable, ranging from 4% to 45% of cases. In other worldwide clinical trials, the mean CIC rate was approximately 23% of cases [21,22].…”
Section: Discussionmentioning
confidence: 88%
“…To this day, no study has investigated the effect of the number of interventions per surgeon per year on patient outcomes or surgical failure and complication rates regarding BoNT. Barba et al investigated the learning curve in residents and only found improvements for operative time, subjective easiness, and perceived tolerability [ 13 ]. No improvements were found concerning the number of valid injections or complications.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors contribute to whether a physician is able to perform a particular medical procedure, including the extent of specific training and skills, which can be considered as an extension of the concept of experience. Recently, there has been great interest in the evaluation of the impact of the degree of experience in terms of the proficiency of medical procedures [ 8 , 9 ]. Learning curves graphically meet this need by representing the impacts of the repetitive task over a defined period, in terms of proficiency parameters, such as duration of procedure, difficulty and grade of autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there is a growing literature on the learning curves in urology and female pelvic floor medicine. For instance, there are some reports on operative cystoscopy for botulinum toxin bladder injections and transurethral resection of the prostate, which showed excellent safety and efficiency even at the beginning of the learning curve [ 9 , 10 , 11 ]. Similar experiences have been published regarding the surgical management of stress urinary incontinence with midurethral slings [ 8 , 12 ].…”
Section: Discussionmentioning
confidence: 99%